Nitric Oxide Plays a Role in Stem Cell Niche Homeostasis through Its Interaction with Auxin . Issue 4 (14th October 2014) - Sanz, Luis; Fernández-Marcos, María; Modrego, Abelardo; Lewis, Daniel R.; Muday, Gloria K.; Pollmann, Stephan; Dueñas, Montserrat; Santos-Buelga, Celestino; Lorenzo, Oscar
Abstract : Nitric oxide regulation of stem cell decisions in Arabidopsis roots is related to auxin biosynthesis, transport, and signaling . Abstract: Nitric oxide (NO ) is a unique reactive nitrogen molecule with an array of signaling functions that modulates plant developmental processes and stress responses. To explore the mechanisms by which NO modulates root development, we used a pharmacological approach and NO -deficient mutants to unravel the role of NO in establishing auxin distribution patterns necessary for stem cell niche homeostasis. Using the NO synthase inhibitor and Arabidopsis ( Arabidopsis thaliana ) NO biosynthesis mutants ( nitric oxide-associated1 [ noa1 ], nitrate reductase1 [ nia1 ] and nia2, and nia1 nia2 noa1 ), we show that depletion of NO in noa1 reduces primary root elongation and increases flavonol accumulation consistent with elevated reactive oxygen species levels. The elevated flavonols are required for the growth effect, because the transparent testa4 mutation reverses the noa1 mutant root elongation phenotype. In addition, noa1 and nia1 nia2 noa1 NO -deficient mutant roots display small root meristems with abnormal divisions. Concomitantly, auxin biosynthesis, transport, and signaling are perturbed. We further show that NO accumulates in cortex/endodermis stem cells and their precursor cells. In endodermal and cortical cells, the noa1 mutant acts synergistically to the effect of the wuschel-related homeobox5 mutation on the proximal meristem, suggesting that NO could play an important role in regulating stem cell decisions, which has been reported in animals.